Typology of Work–Family Balance Among Middle–Aged and Older Japanese Adults - Tomida, Makiko; Nishita, Yukiko; Tange, Chikako; Nakagawa, Takeshi; Otsuka, Rei; Ando, Fujiko; Shimokata, Hiroshi (Frontiers in Psychology, 2022)
This study explores the clusters of work-family balance (WFB) among Japanese middle-aged and older adults and clarifies the characteristics of the derived clusters. Data on working adults (N = 1,351; age range = 40–85 years) were drawn from a pool of participants in the National Institute for Longevity Sciences—Longitudinal Study of Aging. The WFB scale consists of subscales assessing work-family conflict (WFC) and work-family facilitation (WFF). First, a cluster analysis was performed using the WFB scale, and four clusters were extracted. Second, we examined associations between the four clusters and related variables such as demographic characteristics, work, family, and lifestyle factors, social support, and mental health. Our findings showed that the clusters included high-WFC/high-WFF, high-WFC/low-WFF, low-WFC/high-WFF, and low-WFC/low-WFF. Differences were found in related variables among the clusters. Specifically, those in the Low-WFC/High-WFF cluster had a good lifestyle, received the highest levels of social support, and had the fewest mental health issues. Our findings have implications for maintaining sufficient WFB and promoting positive mental health among workers.